2022
DOI: 10.1007/s10934-022-01276-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen doped activated carbon derived from chitosan/hexamethylenetetramine: structural and CO2 adsorption properties

Abstract: Chitosan and chitosan/ hexamethylenetetramine (HMT) macrospheres were prepared respectively by dropping chitosan and chitosan/HMT (in wt/wt ratios of 1:1 and 1:3) solutions in aq. NaOH solution.Here, HMT served as an additional nitrogen precursor for in-situ N-doping with chitosan derived activated carbon (AC). The as-formed macrospheres were impregnated using ZnCl 2 , freeze-dried, and carbonized at 500°C under inert atmosphere to yield ACs of average size 2.6 mm. All the samples were characterized using SEM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Malini and co-workers prepared N-doped porous AC using CS and hexamethylenetetramine (HMT) (in ratios of 1 : 1 and 1 : 3 wt/ wt) as the carbon precursor and an additional nitrogen source, respectively. 191 The CS/HMT-derived AC had a larger N-content and enhanced thermal stability, but as the HMT content increased, the surface characteristics decreased. At 25 °C, the CO 2 adsorption of AC produced from CS was determined to be 97.98 mg g −1 , compared to 72.95 and 55.11 mg g −1 for AC/ HMT (1 : 1) and AC/HMT (1 : 3), respectively.…”
Section: Mechanism For Co 2 Capturementioning
confidence: 94%
“…Malini and co-workers prepared N-doped porous AC using CS and hexamethylenetetramine (HMT) (in ratios of 1 : 1 and 1 : 3 wt/ wt) as the carbon precursor and an additional nitrogen source, respectively. 191 The CS/HMT-derived AC had a larger N-content and enhanced thermal stability, but as the HMT content increased, the surface characteristics decreased. At 25 °C, the CO 2 adsorption of AC produced from CS was determined to be 97.98 mg g −1 , compared to 72.95 and 55.11 mg g −1 for AC/ HMT (1 : 1) and AC/HMT (1 : 3), respectively.…”
Section: Mechanism For Co 2 Capturementioning
confidence: 94%
“…38 On the other hand, chitosan from crab shells and shrimps is a well-known costeffective natural precursor with covalently attached amino functionalities to produce N-doped carbon materials. 39,40 Moreover, it was recently reported that covalently attached amine functionalities produce carbon materials with high nitrogen contents and a suitable hierarchical porous architecture. Nevertheless, these two natural materials have never been used together to synthesize organically induced N/SO x species in carbon materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, the sulfonate groups in sulfonated lignin have been recognized as the sacrificial template to generate the oxygenated CSC moieties and increase the porous architecture of the carbon materials 38 . On the other hand, chitosan from crab shells and shrimps is a well‐known cost‐effective natural precursor with covalently attached amino functionalities to produce N‐doped carbon materials 39,40 . Moreover, it was recently reported that covalently attached amine functionalities produce carbon materials with high nitrogen contents and a suitable hierarchical porous architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan gained a broad range of applications due to the some special features such as ecofriendly nature, abundancy, low cost, easy manipulation, high content of nitrogen, and insolubility in most of the solvents . This biopolymer could be the fascinating precursor for the synthesis of nitrogen-doped carbon (NC) by a thermal decomposition reaction because it could provide both nitrogen and carbon atoms for the construction. This facile, effective, and inexpensive pathway provides NC for various purposes, in particular, it generates an optically active support for the photocatalysts . The obtained NC has some characteristics such as strongly anchoring to the transition metals, high optical activity, generating n-type semiconductor, and sustainability. This kind of semiconductor easily retards charge recombination due to the presence of nitrogen atoms, which leads to the durability of the photocatalyst .…”
Section: Introductionmentioning
confidence: 99%
“… 1 This biopolymer could be the fascinating precursor for the synthesis of nitrogen-doped carbon (NC) by a thermal decomposition reaction because it could provide both nitrogen and carbon atoms for the construction. 2 7 This facile, effective, and inexpensive pathway provides NC for various purposes, in particular, it generates an optically active support for the photocatalysts. 8 The obtained NC has some characteristics such as strongly anchoring to the transition metals, high optical activity, generating n-type semiconductor, and sustainability.…”
Section: Introductionmentioning
confidence: 99%